Impact of a commercially available model-based dose calculation algorithm on treatment planning of high-dose-rate brachytherapy in patients with cervical cancer. (25th January 2018) - Abe, Kota; Kadoya, Noriyuki; Sato, Shinya; Hashimoto, Shimpei; Nakajima, Yujiro; Miyasaka, Yuya; Ito, Kengo; Umezawa, Rei; Yamamoto, Takaya; Takahashi, Noriyoshi; Takeda, Ken; Jingu, Keiichi
Abstract: We evaluated the impact of model-based dose calculation algorithms (MBDCAs) on high-dose-rate brachytherapy (HDR-BT) treatment planning for patients with cervical cancer. Seven patients with cervical cancer treated using HDR-BT were studied. Tandem and ovoid applicators were used in four patients, a vaginal cylinder in one, and interstitial needles in the remaining two patients. MBDCAs were applied to the Advanced Collapsed cone Engine (ACE; Elekta, Stockholm, Sweden). All plans, which were originally calculated using TG-43, were re-calculated using both ACE and Monte Carlo (MC) simulations. Air was used as the rectal material. The mean difference in the rectum D2cm 3 between ACErec-air and MCrec-air was 8.60 ± 4.64%, whereas that in the bladder D2cm 3 was −2.80 ± 1.21%. Conversely, in the small group analysis ( n = 4) using water instead of air as the rectal material, the mean difference in the rectum D2cm 3 between TG-43 and ACErec-air was 11.87 ± 2.65%, whereas that between TG-43 and ACErec-water was 0.81 ± 2.04%, indicating that the use of water as the rectal material reduced the difference in D2cm 3 between TG-43 and ACE. Our results suggested that the differences in the dose–volume histogram (DVH) parameters of TG-43 and ACE were large for the rectum when considerable air (gas) volume was present in it, and that this difference was reduced when the air (gas) volume was reduced. Also, ACE exhibited better dose calculation accuracy than that of TG-43 in this situation. Thus, ACE may be able to calculate the dose more accurately than TG-43 for HDR-BT in treating cervical cancers, particularly for patients with considerable air (gas) volume in the rectum.